The Effectiveness of Implementing the Bidikmisi Program at Jember University - Pratama, Aditya Hardiansyah; Sukidin (Asian Journal of Multidisciplinary Studies, 2024)
Implementing the Bidikmisi program is a government policy to provide access to learning in higher education for underprivileged people with exemplary academic achievements. The Bidikmisi program is carried out according to the 3T principle: on target, on time, and in the right amount. This program is still experiencing various obstacles in its implementation that affect the achievement of program objectives. These obstacles also occur at the University of Jember as one of the tertiary institutions implementing the Bidikmisi program, both in the process of acceptance, implementation, monitoring, and evaluation. This study aims to see the effectiveness of implementing the Bidikmisi program at the University of Jember using evaluation research with descriptive percentage analysis. Respondents in this study were Jember University students receiving the 2017 Bidikmisi program and managers of the Bidikmisi program at Jember University. Data collection techniques using interview methods, observation methods, and questionnaire methods. The analysis results show that implementing the Bidikmisi program at the University of Jember has been very effective as measured by four aspects. The aspect targeting accuracy of the Bidikmisi program has been effective because the program's recipients have met the target criteria. Then the aspect of program socialization has also been running effectively in its implementation. Bidikmisi recipients stated that information could be obtained quickly, clearly, and consistently according to policy. Aspects of achieving program goals have also been very effective, where increasing access and learning opportunities have been completed. Increasing learning achievement has also shown effective results, but achieving the goals of ensuring timely studies and producing independent graduates still needs to be improved, including aspects of program monitoring that still find obstacles that need to be evaluated for future improvements.